Arminius or the Rise of a National Symbol in Literature From Hutten to Grabbe - Kuehnemund, Richard, 1895- (University of North Carolina studies in the Germanic languages and literatures ;, 2020)
This volume provides an evaluation of the ideological significance of the Arminius trope in patriotic German literature. Beginning with the German Humanists and ranging through the works of Hutten, Lohenstein, J. E. Schlegel, Klopstock, Kleist, Grabbe and others. Kuehnemund tracks how Arminius has been deployed as a symbol of the German nation by major intellectual movements and at key points in German history leading up to the Second World War.